Energy Consumption and Economic Growth Nexus: Evidence from Developed Countries in Europe - UCAN, Okyay; ARICIOGLU, Ebru; YUCEL, Fatih (International Journal of Energy Economics and Policy, 2014)
This paper analyzes the relationship between renewable and non-renewable energy consumption and economic growth for a panel of fifteen European Union countries over the period 1990-2011 within a multivariate framework. The heterogeneous panel cointegration tests present a long-run equilibrium relationship between real GDP, renewable and non-renewable energy consumption, greenhouse gas emissions and research and development. The Granger-causality results demonstrate unidirectional causality between non-renewable energy consumption and economic growth. Keywords: renewable energy consumption; non-renewable energy consumption; growth JEL Classifications: C23; O11; O13